Histological evaluation of tissue destruction in mouse tongues caused by cryosurgery - Tadashi Kawai; Atsushi Ogawa; Isao Hoshi; Hiroyuki Yamada; Akira Fujimura (Scars, Burns & Healing, 2024)
Introduction Cryosurgery is recognized as a treatment option for various types of oral lesions. Although cryosurgery is less invasive and easier to perform than surgical treatments, adverse events, such as stomatitis and scarring can occur if the freezing is excessive. There are few studies regarding the effects of cryosurgery on the surrounding soft tissues. Thus, this study investigated the extent of tissue destruction and healing progress in tongues of mice who underwent cryosurgery. Methods Eight-week-old male BALB/c mice were used. An instrument cooled with liquid nitrogen was lightly touched on the right side of the tongue for 5 s, and a second test was performed 10 s later. Histological evaluation was performed 3, 7, and 14 days after cryosurgery. Blood vessels were evaluated with India ink at 1, 3, 7, 14, and 21 days after cryosurgery. Results Destruction of the soft tissue spread to the left side of the tongue after 3 days. At 7 days, it was confirmed that the muscle tissue was in the process of repair and was completely repaired at 14 days. Although blood vessels were not confirmed at 3 days, they were visible after seven days and were confirmed at 21 days all over the tongue. Discussion and Conclusion These results indicated that the tissue destruction caused by cryosurgery was extensive and suggest that the duration and frequency of freezing should be minimized for clinical use. Lay Summary Cryosurgery is a treatment method for various types of oral lesions. Freezing the lesion causes the tissue to collapse, resulting in its disappearance. Although cryosurgery is less invasive and easier to perform than surgical treatments, adverse events, such as stomatitis and scarring can occur if the freezing is excessive. This study investigated the extent of tissue destruction and healing progress in tongues of mice who underwent cryosurgery. The right side of mice tongues were frozen by an instrument cooled with liquid nitrogen for 5 s, and a second test was performed 10 s later. The tissue destruction was evaluated at 3, 7, and 14 days after freezing. Blood vessels were evaluated with India ink at 1, 3, 7, 14, and 21 days after freezing. Tissue destruction spread to the left side of the tongue after 3 days. At 7 days, it was confirmed that the muscle tissue was in the process of repair and was completely repaired at 14 days. Blood vessel repair was confirmed at 21 days in the throughout tongue. These results indicated that the tissue destruction caused by cryosurgery was large and suggest that the duration and frequency of freezing should be minimized for clinical use.